2020
DOI: 10.3390/mi11020203
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Microfluidic Preconcentration and Nucleic Amplification System for Detection of Influenza A Virus H1N1 in Saliva

Abstract: Influenza A viruses are often present in environmental and clinical samples at concentrations below the limit of detection (LOD) of molecular diagnostics. Here we report an integrated microfluidic preconcentration and nucleic amplification system (µFPNAS) which enables both preconcentration of influenza A virus H1N1 (H1N1) and amplification of its viral RNA, thereby lowering LOD for H1N1. H1N1 virus particles were first magnetically preconcentrated using magnetic nanoparticles conjugated with an antibody speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 38 publications
0
22
0
Order By: Relevance
“…For this reason, it is better to pre-concentrate the virus from a large volume sample before nucleic acid extraction. For instance, Kim et al (2020a) designed a microfluidic pre-concentration and nucleic amplification system (FPNAS) in which the anti-H1N1, antibody-conjugated, magnetic nanoparticles pre-concentrated the H1N1 virus from a large volume of saliva and, then, RT-PCR was used to detect the H1N1 virus. This approach improved the LOD by 10 orders of magnitude compared to non-treated samples ( Fig.…”
Section: Potential Biosensors For Point-of-care Sars-cov-2 Detectionmentioning
confidence: 99%
See 1 more Smart Citation
“…For this reason, it is better to pre-concentrate the virus from a large volume sample before nucleic acid extraction. For instance, Kim et al (2020a) designed a microfluidic pre-concentration and nucleic amplification system (FPNAS) in which the anti-H1N1, antibody-conjugated, magnetic nanoparticles pre-concentrated the H1N1 virus from a large volume of saliva and, then, RT-PCR was used to detect the H1N1 virus. This approach improved the LOD by 10 orders of magnitude compared to non-treated samples ( Fig.…”
Section: Potential Biosensors For Point-of-care Sars-cov-2 Detectionmentioning
confidence: 99%
“…6 (A) Schematic describing the operation protocol of on-chip pre-concentration and nucleic acid amplification. Reproduced with permission from ( Kim et al, 2020a ). (B) Workflow of free-flow electrophoretic virus particles at pre-concentration, followed by thermal lysis and gel-electrophoretic nucleic acid extraction.…”
Section: Potential Biosensors For Point-of-care Sars-cov-2 Detectionmentioning
confidence: 99%
“…Various exciting directions are expected for the future of LOC highly integrated devices for diagnostic and therapeutic are some of the interesting applications of LOC devices. For instance, rapid detection of viral infections [152,153] and early detection of cancer biomarkers [154,155] directly from body fluids are some of the highly attractive subjects in this area.…”
Section: Discussion and Future Perspectivesmentioning
confidence: 99%
“…Kim et al recently designed a microfluidic‐based method for detecting H1N1 influenza, and the results suggested that the limit of detection (LOD) of molecular diagnostics for the virus can be lowered by systematically combining immunomagnetic separation and RT‐PCR in one microfluidic device 40 . Moreover, RT‐PCR in situ has been successfully used for the diagnosis of Zika virus 68 .…”
Section: Microfluidic Devicesmentioning
confidence: 99%
“…As a result, these devices may also help detect SARS‐CoV‐2 and accelerate the process of diagnosis and rehabilitation, ultimately lowering the death rate. These devices can use several techniques such as RT‐PCR, RT‐LAMP, nested PCR, nucleic acid hybridization, ELISA, or fluorescence‐based Assays 40‐44 …”
Section: Introductionmentioning
confidence: 99%